Pengembangan Karakter Generasi Alpha melalui Pendampingan Kreativitas Seni Rupa bagi Anak-Anak Sekolah Minggu Gereja Pandu Bandung - Aryani, Dewi Isma; Manurung, Rosida Tiurma; Ida, Ida; Pandanwangi, Ariesa; Dewi, Belinda Sukapura (Bakti Budaya: Jurnal Pengabdian kepada masyarakat, 2024)
With a tridharma vision and mission founded on ICE values, namely Integrity, Care, and Excellence, Universitas Kristen Maranatha is one of the top ten best private university in Indonesia according to THE Impact Rankings 2022. The Pandu Church Sunday School students that attend the Bina Iman Lanjutan (BIL) are the target audience for community service projects. Using decorative buttons, flannel in various colors, and textile coloring markers on a drawstring fabric bag, the implementation approach is carried out through mentoring and creative experimental activities. This program is intended to foster the Alpha Generation's character among the Sunday School students of the Pandu Church. 26 FSRD students, 9 teaching staff from several faculties at Universitas Kristen Maranatha, 27 Sunday School participants, and 6 BIL’s Pandu Church supervisors helped with the offline activities. Participants are able to create crafts out of drawstring fabric bags as a result of this activity.